A Lab Experiment on Committee Hearings: Preferences, Power, and a Quest for Information. Issue 1 (5th May 2016) - Park, Ju Yeon
Abstract : In principle, committees hold hearings to gather and provide information to their principals, but some hearings are characterized as political showcases. This article investigates conditions that moderate committee members' incentives to hold an informative hearing by presenting a game‐theoretic model and a lab experiment. Specifically, it studies when committees hold hearings and which types of hearing they hold by varying policy preferences of committee members and the principal and political gains from posturing. Findings provide new insights to how preferences and power distribution affect individuals' incentives to be informed when they make decisions as members of a committee in many contexts.